Representasi Kekerasan Verbal Tokoh Perempuan Pada Film Serial Sianida: Kajian Analisis Wacana Kritis Norman Fairclough - Sri Rezeki, Tari (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study aims to analyze how verbal violence against female characters is represented in the Cyanide serial film. The approach used is Norman Fairclough's critical discourse analysis which includes three main dimensions: text analysis (micro), discursive practice analysis (meso), and social practice analysis (macro). The main data in this study were obtained from the dialogue transcript of the Cyanide serial film, produced by MVP Entertainment, consisting of 12 episodes. The results of the study indicate that verbal violence against female characters in this film is represented through verbal violence against female characters Jenny, Dita, and Amelia who several times receive sentences with a threatening tone, ridicule, and verbal insults from male characters or those in power such as.